Teriparatide: an innovative and promising strategy for protecting the blood-spinal cord barrier following spinal cord injury - Xiong, Moliang; Feng, Yun; Luo, Caiguang; Guo, Jia; Zeng, Jihuan; Deng, Liang; Xiao, Qiang (Frontiers in Pharmacology, 2024)
The blood-spinal cord barrier (BSCB) is disrupted within minutes of spinal cord injury, leading to increased permeability and secondary spinal cord injury, resulting in more severe neurological damage. The preservation of blood-spinal cord barrier following spinal cord injury plays a crucial role in determining the prognosis. Teriparatide, widely used in clinical treatment for osteoporosis and promoting fracture healing, has been found in our previous study to have the effect of inhibiting the expression of MMP9 and alleviating blood-brain barrier disruption after ischemic stroke, thereby improving neurological damage symptoms. However, there are limited research on whether it has the potential to improve the prognosis of spinal cord injury. This article summarizes the main pathological mechanisms of blood-spinal cord barrier disruption after spinal cord injury and its relationship with Teriparatide, and explores the therapeutic potential of Teriparatide in improving the prognosis of spinal cord injury by reducing blood-spinal cord barrier disruption.